2011
DOI: 10.1007/s10526-011-9376-4
|View full text |Cite
|
Sign up to set email alerts
|

The chemical ecology of Harmonia axyridis

Abstract: In the recent SI of BioControl and resultant book from this working group (Roy et al., 2012), we contributed a review paper on the chemical ecology of the invasive aphidophagous ladybird Harmonia axyridis (Sloggett et al., 2011). This paper focused on both the pure and applied aspects of this subject, including sections on: (1) chemical defence; (2) foods, feeding and reproduction; (3) H. axyridis chemistry, humans and human activity, and (4) future research perspectives.Harmonia axyridis' chemical defence is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 142 publications
0
62
0
Order By: Relevance
“…Infestations of H. axyridis in dwellings have become increasingly problematic (Goetz, 2006;Dutau and Rancé, 2008), causing both annoyance from their number and allergic reactions (Nakazawa et al, 2007;Sloggett et al, 2011). Until now, the only recommended way to avoid these problems was physical removal of the aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infestations of H. axyridis in dwellings have become increasingly problematic (Goetz, 2006;Dutau and Rancé, 2008), causing both annoyance from their number and allergic reactions (Nakazawa et al, 2007;Sloggett et al, 2011). Until now, the only recommended way to avoid these problems was physical removal of the aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the only recommended way to avoid these problems was physical removal of the aggregation. The use of attractants in traps would be more appropriate to control populations of this invasive species and easier to handle for householders (Sloggett et al, 2011). The blends collected during these experiments could be used in the design of such a trap.…”
Section: Discussionmentioning
confidence: 99%
“…Potential of predators and parasitoids to limit H. axyridis numbers Harmonia axyridis is protected chemically against predation and more so than many other coccinellids (Sloggett et al 2011). Many laboratory assays indicate its higher toxicity and/or unpalatability compared to other members of aphidophagous guilds (ladybirds, lacewings) (Phoofolo and Obrycki 1998;Cottrell 2004;Sato and Dixon 2004;Kajita et al 2010;Nedvȇd et al 2010).…”
Section: Homalotylus Spp (Hymenoptera: Encyrtidae)mentioning
confidence: 99%
“…In GC-MS, distinctive prey chemicals or suites of chemicals are isolated from the predator in order to identify diet components (Knutsen and Vogt 1985;Becerro et al 2006). Because ladybirds possess taxonomically-specific defensive alkaloids (Daloze et al 1995), GC-MS of prey alkaloids in predator bodies is particularly appropriate for studying IGP of other ladybird species by H. axyridis (Hautier et al 2008;Sloggett et al 2009;Sloggett et al 2011) and to date are used in the only two published field studies on the ecological impact of H. axyridis (Hautier et al 2008;Hautier et al 2011). In addition to the above technique, the last decade has seen the development of a PCR DNA based approach to identifying the gut contents of predatory invertebrates (King et al 2008).…”
Section: Intraguild Predationmentioning
confidence: 99%
“…In general, DNA detection times are a few to many hours (McMillan et al, 2007;Greenstone et al, 2007), while detection using ELISA, can extend to days (Sopp and Sunderland, 1989;Symondson and Liddell, 1995). Results from GC-MS are highly variable, because target chemicals, especially defensive ones, can be broken down (Sloggett and Davis 2010;Sloggett et al 2011), sequestered or may remain in the predator as unmetabolised compounds. While Sloggett et al (2009) found that hippodamine from single H. convergens eggs persisted on average for 13.5 h in H. axyridis intraguild predators, Hautier et al (2008) found that adaline from a single A. bipunctata first instar larva could persist for many days.…”
Section: Detection Period Of Prey After a Predation Eventmentioning
confidence: 99%